Dietary lecithin improves dressing percentage and decreases chewiness in the longissimus muscle in finisher gilts - Akit, Henny; Collins, Cherie Louise; Fahri, Fahri T.; Hung, Alex Tsungyu; D'Souza, D. N.; Leury, Brian Joseph; Dunshea, Frank Rowland (Elsevier, 2014)
The influence of dietary lecithin at doses of 0, 4, 20 or 80 g/kg fed to finisher gilts for six weeks prior to slaughter on growth performance, carcass quality and pork quality was investigated. M. longissimus lumborum (loin) was removed from 36 pig carcasses at 24 h post-mortem for Warner–Bratzler shear force, compression, collagen content and colour analyses. Dietary lecithin increased dressing percentage (P = 0.009). Pork chewiness and collagen content were decreased by dietary lecithin (P < 0.05, respectively), suggesting that improved chewiness may be due to decreased collagen content. However, dietary lecithin had no effect on shear force, cohesiveness or hardness (P > 0.05, respectively). Dietary lecithin reduced loin muscle L* values and increased a* values (P < 0.05, respectively) but no changes on b* values (P = 0.56). The data showed that dietary lecithin improved dressing percentage and resulted in less chewy and less pale pork.